2011
DOI: 10.1038/msb.2011.59
|View full text |Cite
|
Sign up to set email alerts
|

Cellular reprogramming by the conjoint action of ERα, FOXA1, and GATA3 to a ligand‐inducible growth state

Abstract: Estrogen receptor α (ERα), FOXA1, and GATA3 form a functional enhanceosome in MCF-7 breast carcinoma cell that is significantly associated with active transcriptional features such as enhanced p300 co-activator and RNA Pol II recruitment as well as chromatin opening.The enhanceosome exerts significant impact and optimal transcriptional control in the regulation of E2-responsive genes.The presence of FOXA1 and GATA3 is indispensable in restoring the ERα growth-response machinery in the ERα-negative cells and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
142
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(154 citation statements)
references
References 38 publications
11
142
0
1
Order By: Relevance
“…Recent whole genome analysis identified a GATA3 mutation which exists in 14% of luminal A breast cancer [35]. It was reported that ERα, FOXA1 and GATA3 form a functional enhanceosome to drive the transcription of ERα-regulated genes in breast cancer cells [36,37]. High FOXA1 and GATA3 expression might therefore affect endocrine responsiveness and prognosis in ER-positive breast cancer [38].…”
Section: Discussionmentioning
confidence: 99%
“…Recent whole genome analysis identified a GATA3 mutation which exists in 14% of luminal A breast cancer [35]. It was reported that ERα, FOXA1 and GATA3 form a functional enhanceosome to drive the transcription of ERα-regulated genes in breast cancer cells [36,37]. High FOXA1 and GATA3 expression might therefore affect endocrine responsiveness and prognosis in ER-positive breast cancer [38].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, GATA3 levels increase upon EZH2 silencing, mediating a decrease in bi-lineage cell numbers (Granit et al 2012). Interestingly, the three genes with the greatest negative correlation with VGLL1 and miR-934 in the TCGA dataset were GATA3, ESR1, and FOXA1, which form a functional enhanceosome that regulates the genes driving core ERa functions and that co-operatively modulates the transcriptional networks previously ascribed to ERa alone (Kong et al 2011). Gain and loss of function in vitro studies are currently in progress in our group, using miR-934/VGLL1-negative (MCF7 and T47d) and VGLL1-positive (SKBR3 and MDA-MB-468) cell lines, respectively, that will confirm the suggested role of miR-934 in the modulation of ESR1 expression and the maintenance of a luminal progenitor phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…4a). GATA3 is an important transcriptional regulator in both normal mammary gland development and breast cancer [39][40][41] , and low expression levels of GATA3 are associated with a poor prognosis 42 . Three genes, PTCH1, PPARA and NFIB, exhibit epistatic interactions with GATA3 and also display negatively correlated expression levels with GATA3 (Fig.…”
Section: Resultsmentioning
confidence: 99%